Green Jobs in Tourism Vocational School - Achdiani, Yani; Widiaty, Isma; Ningsih, Mirna Purnama; Mubaroq, Sugeng Rifqi; Latif, Muh Abdul; Farhah Fauziah, Silmi (Universitas Ahmad Dahlan, 2025)
This study employs a comprehensive bibliometric analysis to examine the evolving landscape of Green Jobs in tourism vocational education. Utilizing data from the Scopus database, the research analyzes 93 relevant documents using VOSviewer and Biblioshiny (R) for visualization and analysis. The study reveals significant trends in research output, geographic distribution, and thematic focus areas. Key findings include a marked increase in research activity from 2013 to 2020, with a peak in 2020, followed by a decline potentially influenced by the COVID-19 pandemic. Prominent research clusters center around sustainable development, ecotourism, vocational education, and emerging technologies in tourism. European countries, particularly Italy, emerge as leading contributors, with growing participation from Asia-Pacific and emerging economies. The study highlights the integration of sustainability principles, digital skills, and green human resource management in tourism education curricula. However, it also uncovers research gaps, including limited focus on specific green technologies, climate change adaptation strategies, and crisis management skills. Methodological limitations, such as a scarcity of longitudinal and mixed-methods studies, are noted. The paper proposes future research directions, emphasizing cross-cultural comparative studies and interdisciplinary approaches. It underscores vocational education's role in preparing a sustainability-focused, resilient workforce for the evolving tourism industry. This analysis provides insights for curriculum designers, policymakers, and researchers in aligning educational strategies with the needs of Green Jobs in tourism.